Nghiên cứu tổng hợp sơn điện di anot trên cơ sở polyeste biến tính bằng dầu trẩu và dầu đậu tương Việt Nam - Thiếp và cộng sự, Lê Trọng (Vietnam Journal of Chemistry, 2014)
The results of the synthesis of hydrosoluble polyester used for anodic electrodeposition coating from Viet Nam’s tung and soybean oils are represented in this article. The oil fatty acids characteristic indexes were determined by gas chromatography method with the use of mass spectrophotometer as detector. The molecular weights of polyester were determined by gel permiation chromatography method. The formation process of polyester was studied by infrared spectrum. The changes in viscosity and conductivity of polyester solution in water with change in pH value were studied. The distribution of colloid particles size in solution of pH = 8.2 was determined.